ANALYSIS OF THE ROLE OF LOCAL TAX POLICY IN INCREASING LOCAL REVENUE (PAD) IN 2025 - Yusuf A. Hilman; Ratu Tata Mulia; Rendy Azka Sayid; Nizam Aditya Nicho Saputra (Universitas Islam Majapahit, Indonesia, 2025)
This study aims to analyze the role of regional tax policy in increasing Regional Original Revenue (PAD) by 2025 amidst the dynamics of fiscal decentralization. Regional tax policy is a key instrument in supporting fiscal independence and sustainable regional development. This study found that the implementation of a digital tax system, institutional strengthening, and increased taxpayer awareness significantly contributed to increasing PAD realization, particularly in sectors such as hotels, restaurants, and entertainment. The implementation of Law No. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments provides a new legal basis for strengthening the effectiveness of regional fiscal policy. The results show that the success of tax policy is significantly influenced by the quality of planning, digitalization, public participation, and regional institutional capacity. These findings provide strategic applications for regional governments in designing tax policies that are adaptive, transparent, and pro-community welfare.